Varying levels of X chromosome coalescence in female somatic cells alters the balance of X-linked dosage compensation and is implicated in female-dominant systemic lupus erythematosus - Agnieszka I. Laskowski (Nature Portfolio, 2019)
Abstract The three-dimensional organization of the genome in mammalian interphase nuclei is intrinsically linked to the regulation of gene expression. Whole chromosome territories and their encoded gene loci occupy preferential positions within the nucleus that changes according to the expression profile of a given cell lineage or stage. To further illuminate the relationship between chromosome organization, epigenetic environment, and gene expression, here we examine the functional organization of chromosome X and corresponding X-linked genes in a variety of healthy human and disease state X diploid (XX) cells. We observe high frequencies of homologous chromosome X colocalization (or coalescence), typically associated with initiation of X-chromosome inactivation, occurring in XX cells outside of early embryogenesis. Moreover, during chromosome X coalescence significant changes in Xist, H3K27me3, and X-linked gene expression occur, suggesting the potential exchange of gene regulatory information between the active and inactive X chromosomes. We also observe significant differences in chromosome X coalescence in disease-implicated lymphocytes isolated from systemic lupus erythematosus (SLE) patients compared to healthy controls. These results demonstrate that X chromosomes can functionally interact outside of embryogenesis when X inactivation is initiated and suggest a potential gene regulatory mechanism aberration underlying the increased frequency of autoimmunity in XX individuals.